APATITE IN IGNEOUS SYSTEMS - Piccoli P.M.; Candela P.A. (My University, 2002)
Apatite is a minor but ubiquitous mineral in most igneous rocks. Although the modal proportion of apatite in common rocks is generally low, it can reach high concentrations in enclaves, cumulates, and other rocks of low abundance (i.e., rocks that constitute a small volume of the crust and mantle; e.g., nelsonites). The presence of apatite in most rocks is due not only to its low solubility in naturally occurring melts and aqueous solutions, but also to the limited ability of common rock-forming minerals to accept the amount of phosphorus that occurs in most rocks into their structure. In this paper, we will discuss some aspects of the occurrence, texture, composition, physical chemistry and petrogenetic significance of apatite in felsic rocks (i.e., andesite to rhyolite, and their plutonic analogs), in mafic (i.e., basalts and related rocks, and plutonic analogs), and ultramafic rocks of the Earth’s crust and mantle. Fluorapatite is by far the most common member of apatite family found in igneous rocks. However, most natural fluorapatite contains some chlorine and hydroxyl as well, and these constituents can attain high concentrations in some cases. The other halogens, bromine and iodine, also occur in apatite, but their concentrations are much lower than chlorine and fluorine. Many cations commonly substitute for calcium and phosphorus in apatite, however, they rarely reach concentrations that warrant the definition of a separate mineral species. Apatite can be described by the general formula A5(XO4)3Z (following Sommerauer and Katz-Lehnert 1985). The A-site accommodates large cations (e.g., Ca2+, Sr2+, Pb2+, Ba2+, Mg2+, Mn2+, Fe2+, REE3+, Eu2+, Cd2+, Na+) (Pan and Fleet, Ch. 2 in this volume), and comprises two sites that exhibit VII-fold …